Abnormal placentation at a tertiary care centre - Sharma, Suman S.; Gokhale, Ashish V.; Agarwal, Shonali; Hindocha, Jaydip; Kondhia, Ashini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Placentation abnormalities such as placenta previa, placenta accreta and vasa previa are associated with antepartum and postpartum haemorrhage, which makes them an important cause of serious fetal and maternal morbidity and even mortality in India. In spite of the significant improvement in obstetric care and management and modern transfusion service, antepartum and postpartum bleeding continues to be a significant cause of very high-risk pregnancy. Methods: This is a retrospective study conducted in department of obstetrics and gynecology, Sir Sayaji Hospital, Baroda, for a period of 2 years from January 2018 to December 2019. All cases of placenta previa and morbidly adherent placenta admitted during pregnancy in this period were included in the study. All case records were obtained and carefully analysed to find out the incidence, various types of placenta previa and adherent placenta, its clinical presentation and its outcome in relation to mode of delivery, birth weight, maternal and perinatal morbidity and mortality. Results: The prevalence of placenta previa was 0.87% and was more commonly present among multigravida women (80.3%). Most common type of placenta previa was type 1 in 51 cases (35.9%) cases followed by type 2 in 33 cases (23.2%). 29 cases (20.4%) were of complete placenta. Morbidly adherent placenta comprised 4.2%. Single case (0.7%) was of vasa previa. Out of 142 cases, 12 (8.4%) had atonic PPH and 8 (5.6%) cases underwent peripartum hysterectomy, (12.6%) 18 patients had hemorrhagic shock due to severe blood loss. All cases of perinatal mortality were between 28 to 30 weeks weighing between 1-1.2 kg associated with complete placenta previa in 14 cases and type 3 (incomplete) in 8 cases. There was no maternal mortality in this study Conclusions: Abnormal placentation carries a very high-risk for maternal and fetal outcome. Anticipation, prevention, early detection and appropriate management will result in favorable outcome and will boost the present scenario of management of high-risk pregnancies.